Early Diagnosis of Helicobacter pylori Infection in Vietnamese Patients with Acute Peptic Ulcer Bleeding: A Prospective Study - Duc Trong Quach; Mai Ngoc Luu; Toru Hiyama; Thuy-HuongThi To; Quy Nhuan Bui; Tuan Anh Tran; Binh Duy Tran; Minh-Cong Hong Vo; Shinji Tanaka; Naomi Uemura (Gastroenterology Research and Practice)
Aims. To investigate H. pylori infection rate and evaluate a combined set of tests for H. pylori diagnosis in Vietnamese patients with acute peptic ulcer bleeding (PUD). Methods. Consecutive patients with acute PUB were enrolled prospectively. Rapid urease test (RUT) with 3 biopsies was carried out randomly. Patients without RUT or with negative RUT received urea breath test (UBT) and serological and urinary H. pylori antibody tests. H. pylori was considered positive if RUT or any noninvasive test was positive. Patients were divided into group A (RUT plus noninvasive tests) and group B (only noninvasive tests). Results. The overall H. pylori infection rate was 94.2% (161/171). Groups A and B had no differences in demographic characteristics, bleeding severity, endoscopic findings, and proton pump inhibitor use. H. pylori-positive rate in group A was significantly higher than that in group B (98.2% versus 86.7%, p=0.004). The positive rate of RUT was similar at each biopsy site but significantly increased if RUT results from 2 or 3 sites were combined (p<0.05). Conclusions. H. pylori infection rate in Vietnamese patients with acute PUB is high. RUT is an excellent test if at least 2 biopsies are taken.